Influence of Patient Characteristics on The Type of Insulin Therapy Obtained by Diabetes Type 2 Outpatient in Denpasar Municipality - Febrayana Larasanty, Luh Putu; Dewantara Putra, I GNA.; Dewata Sari, Rhyce; Dede Saputra, Komang; Minanjaya, I GA. Gede; Arya Wiraguna, I Made; Wiracana, I Made (Udayana Journal of Social Sciences and Humanities; Vol 1 No 2 (2017): UJoSSH, September 2017, 2017)
This study aims to investigate the influence of patient characteristics on the choice of insulin therapy in type 2 diabetes mellitus outpatients in Denpasar municipality. This is a descriptive analysis study using the patient's medical records as research material. Patients who meet inclusion and exclusion criteria are being recorded based on their medical records. Characteristics that are taken are age, gender, fasting blood glucose level (FBG), 2-hour postprandial blood glucose level (2-hours PPG) and HbA1c values of patients. Types of insulin therapy gained from patient medical records and drug use report in pharmacy. Characteristics data and type of insulin analyzed using correlation test to determine the effect of the patient characteristics on the selection of insulin therapy. 43 patients became the research subject. Males gendered patients (72.09%) and the patients aged less than 65 years (90.70%) are the dominant characteristics of the research subjects. The average value of FBG of patients is 212 mg / dL; 2-hours PPG 280 mg / dL and HbA1c 10.1%. There is a correlation between sex, age, HbA1c value and FBG with the type of insulin obtained by patients (p <0.05). Based on the results of statistical tests, age and gender have a strong correlation on insulin choice, HbA1c and FBG level has a moderate influence and 2-hours PPG have a weak correlation. Patient characteristics had an influence on the type of insulin choice for diabetes mellitus type 2 outpatient in the Denpasar municipality.